Membrane electrode and preparation method and application thereof

By constructing a gradient cathode catalyst layer in a proton exchange membrane fuel cell, the problems of low catalyst utilization, large mass transfer loss and poor water management capabilities are solved, and fuel cell performance with high power output and long life are achieved.

CN119650720APending Publication Date: 2025-03-18TUNGHSU TECH GRP CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411970660.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-30
Publication Date
2025-03-18

AI Technical Summary

Technical Problem

The problems of low utilization rate of catalysts, large mass transfer loss and poor water management capabilities in the catalytic layer of the existing proton exchange membrane fuel cell.

Method used

By stacking functional layers on both sides of the proton exchange membrane, a layered structure gradient cathode catalyst layer is constructed, and a gradient distributed ionomer multilayer structure is formed using the different perfluorosulfonic acid polymer ion exchange equivalent values ​​and platinum carbon catalyst content of slurry A and slurry B.

Benefits of technology

It improves catalyst utilization, reduces mass transfer losses, improves water management capabilities, and achieves high power output and long-life fuel cell performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119650720A_ABST
    Figure CN119650720A_ABST
Patent Text Reader

Abstract

The invention relates to the field of fuel cells, and discloses a membrane electrode and a preparation method and application thereof. The method comprises the steps that functional layers are arranged on the surfaces of the two sides of a proton exchange membrane in a stacked mode respectively, so that a membrane electrode sequentially containing a first gas diffusion layer, a first cathode slurry layer, a second cathode slurry layer, the proton exchange membrane, an anode catalyst layer and a second gas diffusion layer is obtained; the first cathode slurry layer and the second cathode slurry layer are respectively formed by coating slurry A and slurry B; the anode catalyst layer is formed by coating slurry C; each of the slurry A, the slurry B and the slurry C contains an alcohol solvent, water, a perfluorosulfonic acid polymer and a platinum-carbon catalyst; and the ion exchange equivalent value of the perfluorosulfonic acid polymer contained in the slurry A is at least 200 higher than the ion exchange equivalent value of the perfluorosulfonic acid polymer contained in the slurry B. According to the method for preparing the membrane electrode, the utilization rate of the catalyst is increased, the mass transfer loss is reduced, and the method is an effective strategy for achieving high-power output and long service life.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of fuel cells, and in particular to a membrane electrode and a preparation method and application thereof. Background Art

[0002] Proton exchange membrane fuel cells (PEMFCs) are recognized as clean energy devices due to their high energy conversion efficiency, fast low-temperature start-up, and zero pollution. However, their high price and poor durability severely restrict their large-scale commercial application. Compared with the hydrogen oxidation reaction (HOR) kinetics on the anode catalyst layer (ACL), the oxygen reduction reaction (ORR) kinetics on the cathode catalyst layer (CCL) are slow.

[0003] Among them, the membrane electrode (MEA) is the heart of PEMFC, and the membrane electrode catalyst layer (CL) is the core part of MEA, which is the place where electrochemical reactions occur. CLs are usually composed of carbon-supported platinum nanoparticles and ionomers. Among them, the carbon-supported catalyst particles conduct electrons, while the ionomer is responsible for conducting protons, which is crucial for achieving ionic conductivity, enhancing stability and improving interphase reactions. The two together form a complex mesh porous structure that can conduct reaction gases and water.

[0004] CN111584880A discloses a low-platinum proton exchange membrane fuel cell membrane electrode and its preparation method. The catalyst layer of the membrane electrode provided is prepared by using a porous material and a catalyst filled in the porous material. The amount of platinum used is reduced by adjusting the structure of the membrane electrode catalyst layer. The partial structure ordering process is adopted to adjust the structure of the membrane electrode catalyst layer to reduce the amount of platinum used and reduce the cost of the fuel cell. Compared with the traditional membrane electrode, the membrane electrode adopts a partially ordered structure, which can effectively improve the catalyst utilization rate, reduce the catalyst loading, overcome the membrane electrode swelling problem, and is easy to scale up, which is conducive to mass production. However, due to the use of a porous material structure, the membrane electrode prepared by it has a large interface effect, and the gas is unevenly distributed in the catalyst layer. The uniform distribution of the platinum catalyst will cause catalyst waste in the catalyst layer, reducing the utilization rate of the platinum catalyst.

[0005] Therefore, optimizing the composition and structure of the cathode catalyst layer (CCL) is crucial to improve the performance and durability of MEA. Summary of the invention

[0006] The purpose of the present invention is to overcome the problems of low catalyst utilization, large mass transfer loss and poor water management capability in the catalyst layer of a proton exchange membrane fuel cell in the prior art.

[0007] In order to achieve the above-mentioned object, the first aspect of the present invention provides a method for preparing a membrane electrode, the method comprising: laminating functional layers on both sides of a proton exchange membrane to obtain a membrane electrode sequentially comprising a first gas diffusion layer, a first cathode slurry layer, a second cathode slurry layer, a proton exchange membrane, an anode catalyst layer and a second gas diffusion layer;

[0008] The first cathode slurry layer and the second cathode slurry layer are formed by coating slurry A and slurry B respectively; the anode catalyst layer is formed by coating slurry C;

[0009] The slurry A, the slurry B and the slurry C all contain an alcohol solvent, water, a perfluorosulfonic acid polymer and a platinum-carbon catalyst;

[0010] The ion exchange equivalent value of the perfluorosulfonic acid polymer contained in the slurry A is at least 200 higher than the ion exchange equivalent value of the perfluorosulfonic acid polymer contained in the slurry B;

[0011] The slurry C is the same as or different from the slurry A or the slurry B.

[0012] The second aspect of the present invention provides a membrane electrode prepared by the method described in the first aspect.

[0013] The third aspect of the present invention provides the use of the membrane electrode described in the second aspect in a proton exchange membrane fuel cell.

[0014] Through the above technical solution, the present invention has at least the following advantages:

[0015] The method for preparing a membrane electrode provided by the present invention constructs a layered structure gradient cathode catalyst layer (CCL), improves catalyst utilization, reduces mass transfer loss, and is an effective strategy for achieving high power output and long life.

[0016] The method for preparing a membrane electrode provided by the present invention improves the overall performance of a membrane electrode (MEA), enhances the mass transfer in a proton exchange membrane fuel cell (PEMFC), and improves the water management capability. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] Figure 1 It is a partial structural schematic diagram of the first gas diffusion layer, the first cathode slurry layer, the second cathode slurry layer and the proton exchange membrane in the membrane electrode prepared by the present invention. DETAILED DESCRIPTION

[0018] The endpoints and any values ​​of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.

[0019] In the present invention, the carbon paper is a carbon fiber composite paper material, which is mainly made of short-cut carbon fibers and has a fiber porous structure, and can establish an effective channel for the conduction of gas and water.

[0020] In the present invention, the perfluorosulfonic acid polymer is a polymer having a sulfonic acid group (-SO3 - ) or F-type polymer having a sulfonyl fluoride group (-SO3F) is provided in the form of a perfluorosulfonic acid polymer membrane solution.

[0021] In the present invention, the ion exchange equivalent value (EW value) refers to the molar mass required for each ion exchange site in the polymer when performing an ion exchange reaction.

[0022] In the present invention, SSC represents short side chain, Ionomer represents ionomer, PEM represents proton exchange membrane, LSC represents long side chain, and GDL represents gas diffusion layer.

[0023] As mentioned above, the first aspect of the present invention provides a method for preparing a membrane electrode, the method comprising: laminating functional layers on both sides of a proton exchange membrane to obtain a membrane electrode sequentially comprising a first gas diffusion layer, a first cathode slurry layer, a second cathode slurry layer, a proton exchange membrane, an anode catalyst layer and a second gas diffusion layer;

[0024] The first cathode slurry layer and the second cathode slurry layer are formed by coating slurry A and slurry B respectively; the anode catalyst layer is formed by coating slurry C;

[0025] The slurry A, the slurry B and the slurry C all contain an alcohol solvent, water, a perfluorosulfonic acid polymer and a platinum-carbon catalyst;

[0026] The ion exchange equivalent value of the perfluorosulfonic acid polymer contained in the slurry A is at least 200 higher than the ion exchange equivalent value of the perfluorosulfonic acid polymer contained in the slurry B;

[0027] The slurry C is the same as or different from the slurry A or the slurry B.

[0028] Preferably, the ion exchange equivalent value of the perfluorosulfonic acid polymer contained in the slurry A is 950-1300, and the ion exchange equivalent value of the perfluorosulfonic acid polymer contained in the slurry B is 750-900. The inventors of the present invention unexpectedly found that in this preferred case, the technical solution of the present invention can further improve the catalyst utilization rate and further reduce mass transfer loss.

[0029] Preferably, in the slurry A, the weight ratio of the perfluorosulfonic acid polymer to the platinum-carbon catalyst in terms of carbon content is 0.8-1.2: 1. The inventors have found that in this preferred case, the technical solution of the present invention can further improve catalyst utilization and further reduce mass transfer loss.

[0030] Preferably, in the slurry B, the weight ratio of the perfluorosulfonic acid polymer to the platinum-carbon catalyst in terms of carbon content is 0.8-1.2:1.

[0031] Preferably, the solid content of the slurry A and the slurry B at 25° C. is independently 8-15 wt %.

[0032] Preferably, in the slurry A, the weight ratio of water to isopropanol is 0.7-0.9:1.

[0033] Preferably, in the slurry A, the weight ratio of platinum to carbon in the platinum-carbon catalyst is 0.2-1.5:1, for example, it can be 0.25:1 or 0.667:1 or 1:1 or 1.5:1.

[0034] Preferably, in the slurry B, the weight ratio of water to isopropanol is 0.7-0.9:1.

[0035] Preferably, in the slurry B, the weight ratio of platinum to carbon in the platinum-carbon catalyst is 0.2-1.5:1, for example, it can be 0.25:1 or 0.667:1 or 1:1 or 1.5:1.

[0036] Preferably, the slurry C is the same as the slurry A.

[0037] Preferably, the solid content of the slurry C at 25° C. is 8-15 wt %.

[0038] Preferably, in the slurry C, the weight ratio of water to isopropanol is 0.7-0.9:1.

[0039] Preferably, in the slurry C, the weight ratio of platinum to carbon in the platinum-carbon catalyst is 0.2-1.5:1, for example, it can be 0.25:1 or 0.667:1 or 1:1 or 1.5:1.

[0040] Preferably, based on the platinum content in the platinum-carbon catalyst in the slurry A, relative to 1 cm 2 The proton exchange membrane, the coating amount of the slurry A is 0.1-0.3 mg Pt .

[0041] Preferably, based on the platinum content in the platinum-carbon catalyst in the slurry B, relative to 1 cm 2 The proton exchange membrane, the coating amount of the slurry B is 0.25-0.35 mg Pt .

[0042] Preferably, based on the platinum content in the platinum-carbon catalyst in the slurry C, relative to 1 cm 2 The proton exchange membrane, the coating amount of the slurry C is 0.025-0.15 mg Pt .

[0043] Preferably, the method further comprises: drying the first cathode slurry layer, the second cathode slurry layer, and the anode catalyst layer respectively.

[0044] Preferably, the drying temperature is 60-70° C., and the drying method is oven drying.

[0045] According to a preferred embodiment, the present invention Figure 1 A partial structural schematic diagram of the first gas diffusion layer, the first cathode slurry layer, the second cathode slurry layer, and the proton exchange membrane in the membrane electrode prepared as above is provided; Figure 1 In the present invention, SSC ionomer catalyst slurry is applied on the side close to the PEM proton exchange membrane, and LSC ionomer catalyst slurry is applied on the side close to the GDL, and a gradient cathode catalyst layer (CCL) is successfully created.

[0046] The present invention has no particular limitation on the coating method. For example, the coating can be performed by a slit coating method.

[0047] Preferably, the first gas diffusion layer and the second gas diffusion layer are both carbon paper with a thickness of 100-200 μm.

[0048] As mentioned above, the second aspect of the present invention provides a membrane electrode prepared by the method described in the first aspect.

[0049] As mentioned above, the third aspect of the present invention provides the use of the membrane electrode described in the second aspect in a proton exchange membrane fuel cell.

[0050] The present invention will be described in detail below by way of examples. In the following examples, unless otherwise specified, the drugs and reagents used are all commercially available products.

[0051] Platinum-carbon catalyst: The brand is Japan Tanaka Precious Metals Platinum-carbon catalyst, model / grade is TEC10EA50E.

[0052] In slurry A:

[0053] Perfluorosulfonic acid polymer (A-1): a perfluorosulfonic acid polymer membrane solution purchased from Chemours, with a model / brand of Nafion D2020; the mass of the perfluorosulfonic acid polymer therein is 20 wt %, and the ion exchange equivalent value is 1000.

[0054] In slurry B:

[0055] Perfluorosulfonic acid polymer (B-1): a perfluorosulfonic acid polymer membrane solution purchased from Solvay Group, model / brand DFPSA-2179; the mass of the perfluorosulfonic acid polymer therein is 10 wt %, and the ion exchange equivalent value is 790.

[0056] In slurry C:

[0057] Perfluorosulfonic acid polymer (C-1): a perfluorosulfonic acid polymer membrane solution purchased from Chemours, with a model / brand of Nafion D2020; the mass of the perfluorosulfonic acid polymer is 20 wt %, and the ion exchange equivalent value is 1000.

[0058] The proton exchange membrane was purchased from Gore Company of the United States, with a model / brand of M788.12.

[0059] In the following examples, the area of ​​the effective proton exchange membrane is 5×5 cm; in slurry A, slurry B and slurry C, the weight ratio of platinum to carbon in the platinum carbon catalyst is 1:1; the coating amounts of slurry A and slurry B are respectively measured based on the platinum content in the platinum carbon catalyst in the slurry.

[0060] The following examples are used to illustrate the method for preparing a membrane electrode provided by the present invention.

[0061] Example 1

[0062] Functional layers are stacked on both sides of the proton exchange membrane, and the specific operations are as follows:

[0063] (1) weighing a perfluorosulfonic acid polymer A-1, a platinum-carbon catalyst, an alcohol solvent (isopropanol) and water, mixing them, and dispersing them by mechanical stirring and ultrasonic wave to form a slurry A (weight 50 g); the weight ratio of water to isopropanol is 0.8:1;

[0064] Weighing perfluorosulfonic acid polymer B-1, platinum-carbon catalyst, alcohol solvent (isopropanol) and water, mixing, and forming slurry B (weight 50 g) by mechanical stirring and ultrasonic dispersion; the weight ratio of water to isopropanol is 0.8:1;

[0065] and weighing a perfluorosulfonic acid polymer C-1, a platinum-carbon catalyst, an alcohol solvent (isopropanol) and water, mixing them, and forming a slurry C (weight 50 g) by mechanical stirring and ultrasonic dispersion; the weight ratio of water to isopropanol is 0.8:1;

[0066] (2) Slurry B was coated by slit coating (coating amount was 0.3 mg) Pt / cm 2 proton exchange membrane) on one side surface of the proton exchange membrane to form a second cathode slurry layer, and drying it at 65° C.;

[0067] Slurry A was applied (the coating amount was 0.1 mg Pt / cm 2 proton exchange membrane) on the surface of the second cathode slurry layer to form a first cathode slurry layer, and drying it at 65° C.;

[0068] And slurry C is coated (coating amount is 0.1 mg Pt / cm 2 proton exchange membrane) on the other side of the proton exchange membrane to form an anode catalyst layer, and drying it at 65° C.;

[0069] (3) A gas diffusion layer (carbon paper with a thickness of 170 μm) is laminated onto the upper and lower surfaces of the first cathode slurry layer and the anode catalyst layer by hot pressing to obtain a membrane electrode containing, in sequence, a first gas diffusion layer, a first cathode slurry layer, a second cathode slurry layer, a proton exchange membrane, an anode catalyst layer and a second gas diffusion layer.

[0070] The specific materials and their proportions of this embodiment are shown in Table 1.

[0071] The remaining examples were prepared using the same preparation method as Example 1, except that the specific materials and their proportions were different, as shown in Table 1.

[0072] Table 1

[0073]

[0074]

[0075] Example 4

[0076] This example is carried out in a similar manner to that of Example 1, except that the components and proportions of the slurry A of this example remain unchanged, and the platinum content in the platinum-carbon catalyst in the slurry A is calculated relative to 1 cm 2 The coating amount of the proton exchange membrane was adjusted to 0.2 mg. Pt ; While keeping the components and ratio of slurry B of this embodiment unchanged, the platinum content in the platinum-carbon catalyst in slurry B is relative to 1cm 2 The coating amount of the proton exchange membrane was adjusted to 0.2 mg. Pt , and obtain a cathode catalytic coating.

[0077] A membrane electrode is obtained which sequentially contains a first gas diffusion layer, a first cathode slurry layer, a second cathode slurry layer, a proton exchange membrane, an anode catalyst layer and a second gas diffusion layer.

[0078] Comparative Example 1

[0079] This comparative example is carried out in a similar manner to Example 1, except that the method steps of this comparative example are specifically as follows:

[0080] Measured by the platinum content in the platinum-carbon catalyst in slurry A, relative to 1 cm 2 A proton exchange membrane is prepared by sequentially coating slurry A on one side of the proton exchange membrane in amounts of 0.1 mg, 0.2 mg, and 0.1 mg using a slit coating method to form a three-layer cathode slurry layer;

[0081] And slurry C is applied (the coating amount is 0.1 mg / cm 2 A proton exchange membrane) is formed on the other side surface of the proton exchange membrane to form an anode catalyst layer;

[0082] A membrane electrode is obtained which sequentially contains a first gas diffusion layer, a third cathode slurry layer, a first cathode slurry layer, a second cathode slurry layer, a proton exchange membrane, an anode catalyst layer and a second gas diffusion layer.

[0083] Test Case

[0084] All membrane electrodes obtained in the example were assembled into single cells and polarization curve tests were performed. The membrane electrode assembly (MEA) was first activated, and then the polarization curve was tested in a H2 / O2 atmosphere (volume flow ratio of 76sccm / 68sccm). The single cell test temperature was 75°C, the relative humidity was 100%, and the active area was 25cm 2 .

[0085] The initial electrical performance test results are shown in Table 2, and the electrical performance test results after durability are shown in Table 3.

[0086] Table 2

[0087] <![CDATA[Current density (A cm -2 )]]> Voltage (V) <![CDATA[Peak power density (W cm -2 )]]> Example 1 2 0.711 1.422 Example 2 2 0.707 1.414 Example 3 2 0.701 1.402 Example 4 2 0.685 1.37 Comparative Example 1 2 0.658 1.316

[0088] Table 3

[0089] <![CDATA[Current density (A cm -2 )]]> Voltage (V) <![CDATA[Peak power density (W cm -2 )]]> Example 1 2 0.692 1.384 Example 2 2 0.685 1.370 Example 3 2 0.676 1.352 Example 4 2 0.645 1.29 Comparative Example 1 2 0.602 1.204

[0090] It can be seen from Tables 2 and 3 that the membrane electrode (MEA) with a cathode catalyst layer (CCL) gradient of the present invention exhibits excellent electrochemical performance, and the cell voltage reaches 0.711 V@2 A cm -2 The polarization curve of the battery was tested after 5000 voltage cycles. Compared with the initial performance, the performance of the membrane electrode (MEA) only decreased by 0.019V@2A cm -2 This shows that the SSC ionomer with low EW contains more sulfonic acid groups, which makes it have more proton channels, which is beneficial to the transport of protons in the cathode catalyst layer (CCL); the LSC ionomer with high EW value has a longer backbone, which increases the repulsive force between the hydrophilic and hydrophobic regions, making it more difficult for water to aggregate and increasing the mass transfer rate.

[0091] It can be seen from the above results that the present invention improves the mass transfer loss and water management problems and increases the activity and durability of the proton exchange membrane fuel cell (PEMFC) by designing a multilayer structure CCL with a gradient distribution of ionomers.

[0092] In summary, the gradient cathode catalyst layer (CCL) design of the present invention is an effective way to achieve high power and long life fuel cells.

[0093] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.

Claims

1. A method for preparing a membrane electrode, characterized in that: The method comprises: laminating functional layers on both sides of the proton exchange membrane to obtain a membrane electrode which sequentially contains a first gas diffusion layer, a first cathode slurry layer, a second cathode slurry layer, a proton exchange membrane, an anode catalyst layer and a second gas diffusion layer; The first cathode slurry layer and the second cathode slurry layer are formed by coating slurry A and slurry B respectively; the anode catalyst layer is formed by coating slurry C; The slurry A, the slurry B and the slurry C all contain an alcohol solvent, water, a perfluorosulfonic acid polymer and a platinum-carbon catalyst; The ion exchange equivalent value of the perfluorosulfonic acid polymer contained in the slurry A is at least 200 higher than the ion exchange equivalent value of the perfluorosulfonic acid polymer contained in the slurry B; The slurry C is the same as or different from the slurry A or the slurry B.

2. The method according to claim 1, characterized in that The ion exchange equivalent value of the perfluorosulfonic acid polymer contained in the slurry A is 950-1300, and the ion exchange equivalent value of the perfluorosulfonic acid polymer contained in the slurry B is 750-900.

3. The method according to claim 1, characterized in that In the slurry A, the weight ratio of the perfluorosulfonic acid polymer to the platinum-carbon catalyst in terms of carbon content is 0.8-1.2:1; And / or, in the slurry B, the weight ratio of the perfluorosulfonic acid polymer to the platinum-carbon catalyst in terms of carbon content is 0.8-1.2:

1.

4. The method according to any one of claims 1 to 3, characterized in that: The solid content of the slurry A and the slurry B at 25° C. is independently 8-15 wt %; and / or, in the slurry A, the weight ratio of water to isopropanol is 0.7-0.9:1; And / or, in the slurry B, the weight ratio of water to isopropanol is 0.7-0.9:

1.

5. The method according to any one of claims 1 to 3, characterized in that: The solid content of the slurry C at 25° C. is 8-15 wt %; And / or, in the slurry C, the weight ratio of water to isopropanol is 0.7-0.9:

1.

6. The method according to any one of claims 1 to 3, characterized in that: Based on the platinum content in the platinum-carbon catalyst in the slurry A, relative to 1 cm 2 The proton exchange membrane, the coating amount of the slurry A is 0.1-0.3 mg Pt ; and / or, based on the platinum content in the platinum-carbon catalyst in the slurry B, relative to 1 cm 2 The proton exchange membrane, the coating amount of the slurry B is 0.25-0.35 mg Pt .

7. The method according to any one of claims 1 to 3, characterized in that: Measured by the platinum content in the platinum-carbon catalyst in the slurry C, relative to 1 cm 2 The proton exchange membrane, the coating amount of the slurry C is 0.025-0.15 mg Pt .

8. The method according to any one of claims 1 to 3, characterized in that: The first gas diffusion layer and the second gas diffusion layer are both carbon papers with a thickness of 100-200 μm.

9. A membrane electrode prepared by the method according to any one of claims 1 to 8.

10. Use of the membrane electrode according to claim 9 in a proton exchange membrane fuel cell.

Citation Information

Patent Citations

  • Low-platinum proton exchange membrane fuel cell membrane electrode and preparation method thereof

    CN111584880A